1966
DOI: 10.1002/pol.1966.150040920
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation of high polymers

Abstract: SynopsisA new class of polymeric materials has been prepared and subjected to preliminary These materials were obtained by hydroformylation of diene-based poly-evaluation. mers. The olefinic bonds were saturated and aldehyde groups attached:The extent of reaction may be varied a t will up to 100% double bond conversion. The properties of these polymers are dominated by the active aldehyde groups. One of the chief characteristics of simple aldehydes is their ability to polymerize forming mainly aldehyde trimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The hydroformylation of alkenes using syngas (carbon monoxide and hydrogen) is a well-known transformation that has been used for a long time in many industrial processes. The first application of this methodology for the introduction of formyl groups into olefinic polymers was reported in 1966 . The hydroformylation of different diene-based polymers was performed with the dicobalt octacarbonyl complex as catalyst, requiring harsh conditions.…”
Section: Metal-catalyzed Postpolymerization Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroformylation of alkenes using syngas (carbon monoxide and hydrogen) is a well-known transformation that has been used for a long time in many industrial processes. The first application of this methodology for the introduction of formyl groups into olefinic polymers was reported in 1966 . The hydroformylation of different diene-based polymers was performed with the dicobalt octacarbonyl complex as catalyst, requiring harsh conditions.…”
Section: Metal-catalyzed Postpolymerization Processesmentioning
confidence: 99%
“…The first application of this methodology for the introduction of formyl groups into olefinic polymers was reported in 1966. 33 The hydroformylation of different diene-based polymers was performed with the dicobalt octacarbonyl complex as catalyst, requiring harsh conditions. Complete conversions were achieved at 180 °C for 3 h, with an initial H 2 :CO pressure of 2400 psi (Scheme 5A).…”
Section: Metal-catalyzed Postpolymerization Processesmentioning
confidence: 99%
“…The catalytic hydroformylation of unsaturated polymers is a process by which aldehyde groups are introduced into the backbone polymer by a treatment with H 2 and CO in the presence of a catalyst. The common catalyst generally used for this process is a Co or Rh complex 2–10. The most effective catalysts for the hydroformylation of CC are rhodium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the hydroformylation of diene polymers, that is, polybutadiene (PBD) and poly(styrene butadiene) (SBR), were carried out in the presence of rhodium catalysts. However, the earliest study showed that the hydroformylation of 1,4‐PBD and high‐styrene SBR could be achieved at high pressures and temperatures with a cobalt catalyst,2 but there was considerable gel formation during this process. The first report of the use of HRh(CO)(PPh 3 ) 3 in the hydroformylation of a polypentenamer was by Sanui et al,3 and the reaction was carried out under moderate conditions with no gel formation.…”
Section: Introductionmentioning
confidence: 99%
“…Functional polymers are generally prepared by the polymerization of monomers containing the desired functional groups. As these polymerizations are sometimes associated with potential problems, much attention has been paid to the development of the catalytic functionalization of diene-based elastomers. The production of polymers with carboxylated backbones is of particular interest due to potential applications of such polymers in films and surface coating…”
Section: Introductionmentioning
confidence: 99%